3D printing of a composite iPP/quill of chicken feathers functionalized with pimelic acid. Issue 12 (27th September 2022) - Patiño‐Almanza, Rodrigo; Flores‐Hernandez, Cynthia G.; Rivera‐Armenta, José Luis; Strachota, Adam; Almendarez‐Camarillo, Armando
Abstract: In this work, the thermomechanical properties of an isotactic polypropylene (iPP)/quill composite were evaluated. This reinforcement was added at 0.5, 1.0 and 5.0 wt% in the iPP matrix. The reinforcement was previously subjected to alkaline treatment with NaOH (QT) and chemical functionalization with pimelic acid (PA) to produce an effective β‐crystal nucleating agent. This functionalization was characterized by Fourier transform infrared spectroscopy (FTIR), showing the presence of a new band at 1571 cm −1 associated with the carboxylate group of pimelic acid, indicating a bond between PA and the quill surface. The internal geometry of the specimens obtained by 3D printing were studied by scanning electron spectroscopy (SEM). The effectiveness of the modified reinforcement as a promoter of the β‐crystalline phase was evaluated by differential scanning calorimetry (DSC) and wide angle X‐ray scattering (WAXD) under non‐isothermal crystallization conditions due to the 3D printing process. The composite that showed a higher K β index was 1.0% with a value of 64% by DSC and 65% by WAXD. Furthermore, the thermomechanical properties were characterized by dynamic mechanical analysis (DMA) where, for the 0.5% and 1.0% composites, the storage modulus ( E ') was higher compared to neat iPP. However, for the 5.0% composite the E ' values were lower. Abstract : Process of manufacturing 3D printed composites from quill of chicken feathers.